Influence of automatic voltage control on small signal stability of photovoltaic system - Jianhua Zhu; Zhibo Li; Xiaoming Yue; Yonghui Nie (Energy Reports, 2022)
In order to solve the problem of large delay and uncertain impact on the system when traditional automatic voltage control is used in photovoltaic power station system control, a small signal analysis model of photovoltaic grid connected system including automatic voltage control is established. Firstly, considering that the actual automatic voltage control system contains dead time and delay link, the continuous dead time model of photovoltaic system is defined; Then, considering the nonlinear part of automatic voltage control, the small disturbance model of photovoltaic grid connected system with dead time and delay part is derived. The small disturbance model of photovoltaic system is formed by using the linearization principle, which is used to describe the expressions of damping torque and synchronous torque of photovoltaic system; Then, the expressions of PV active power increment, power angle increment and speed increment are obtained by small signal model; Finally, the validity of the model is verified by the comparison of theoretical calculation and simulation results. The results show that the proposed model can describe the damping component and synchronous component effect of photovoltaic system under disturbance, and provide a reference for the study of photovoltaic stability.